MAIN COMPLICATIONS AND CLINICAL OUTCOMES OF ELDERLY TRAUMA VICTIMS ADMITTED TO INTENSIVE THERAPY UNIT - Ana Cristina Carvalho da Costa; Renata Costa Fortes (Universidade Federal do Paraná, 2018)
Objective: To identify the main complications and the clinical outcome of elderly trauma victims admitted to the Intensive Care Unit of a referral hospital of Distrito Federal between July 2012 and July2014. Method: Retrospective analytical study that uses medical records. Data were analyzed using Chi-Square and Mann-Whitney tests, and a significance value of p <0.05 was considered. Results: Most of the 91 elderly were men, whose mechanism of injury was falls from standing height. The main complications were pulmonary infection, tracheostomy due to prolonged intubation and septic shock. There was a high mortality rate: 38 (41.7%), associated with male gender (p = 0.029), other external causes (p = 0.03), septic shock (p = 0.039) and dialysis (p = 0.015). Conclusion: The severe condition of the patients favored the occurrence of multiple complications during hospitalization in intensive care. However, despite the worst prognosis, the elderly may survive the trauma and its associated complications.